Simulating radiation damage cascades in graphite - Christie, H.; Robinson, M.; Roach, D.; Ross, D.; Suarez-Martinez, I.; Marks, Nigel (Elsevier Ltd, 2015)
Molecular dynamics simulation is used to study radiation damage cascades in graphite. High statistical precision is obtained by sampling a wide energy range (100-2500 eV) and a large number of initial directions of the primary knock-on atom. Chemical bonding is described using the Environment Dependent Interaction Potential for carbon. Graphite is found to exhibit a radiation response distinct from metals and oxides primarily due to the absence of a thermal spike which results in point defects and disconnected regions of damage. Other unique attributes include exceedingly short cascade lifetimes and fractal like atomic trajectories. Unusually for a solid, the binary collision approximation is useful across a wide energy range, and as a consequence residual damage is consistent with the Kinchin-Pease model. The simulations are in agreement with known experimental data and help to clarify substantial uncertainty in the literature regarding the extent of the cascade and the associated damage.